Implementasi Model Pembelajaran Project Based Learning Berbantuan Media Jari Tangan dalam Pembelajaran Matematika Kelas I SD Negeri Podorejo 02 Kota Semarang - Fauza Cahya Paradisa; Asrilia Putri Solicha; Vina Indriana Rukmana; Lutfi Azzahro; Eliana Putri Salsabila; Trimurtini (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
Mathematics learning is very important in forming the basis of understanding and mathematical skills that are essential for the intellectual development of students. The results of interviews and observations of learning mathematics in grade I SD Negeri Podorejo 02 students still cannot focus their attention during learning, passive, and low learning outcomes. The focus of this research is to describe the implementation of the Project Based Learning model with the help of Finger Hands media in learning mathematics in grade I SD Negeri Podorejo 02 Semarang City on subtraction material and describe learning outcomes in the aspects of knowledge, attitudes, and skills. The research method used is descriptive qualitative research. The data collection techniques used were interviews, observations, written tests, and rubrics for assessing attitudes and skills. The results of the implementation of the Project Based Learning model in class I at SDN Podorejo 02 Semarang City. The average score increase from pretest to posttest was 14.2. Before the implementation of the model, the complete score was 54.2%, with an incomplete score of 45.8%. After implementing the model, the score was 91.7% complete, with 8.3% incomplete. The skill assessment was calculated in the very good category with 88% while the attitude assessment was calculated in the very good category with 100%. So that by implementing the Project Based Learning model with the help of Finger Hands media in learning mathematics in class I SD Negeri.